1985
DOI: 10.3354/meps022107
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria as a food source for microzooplankton in the Schlei Fjord and Baltic Sea with special references to ciliates

Abstract: In situ investigations revealed that number and biomass of microzooplankton increased with eutrophication along the length of the Schlei Fjord (FRG). The same observation was made for total bacterial numbers and biomass. Microzooplankton of the Schlei and total bacterial numbers showed a minimum in winter and major periods of development in late summer/autumn and spring. Usually the microzooplankton biomass in the Schlei was greater than the bacterial biomass. In contrast. the bacterial biomass for 5 of 6 stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 24 publications
7
59
0
1
Order By: Relevance
“…1) and almost no algal cells suggested that ciliates cannot survive exclusively on bacwithin the size range of 2-6 pm were available. Typical teria in pelagic systems because they require high bacterial raptorial feeders, such as prostomatids, had to be at least concentrations (Fenchel 1980;Gast 1985;Stoecker 1988) partly food limited because the phytoplankton compothat are usually found only in specific environments, such sition became dominated by large algae throughout the as the chemoclinc, oxycline, etc. (Fenchel et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…1) and almost no algal cells suggested that ciliates cannot survive exclusively on bacwithin the size range of 2-6 pm were available. Typical teria in pelagic systems because they require high bacterial raptorial feeders, such as prostomatids, had to be at least concentrations (Fenchel 1980;Gast 1985;Stoecker 1988) partly food limited because the phytoplankton compothat are usually found only in specific environments, such sition became dominated by large algae throughout the as the chemoclinc, oxycline, etc. (Fenchel et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…One Nodularia agglomerate of l cm length and 0.5 cm diameter can be colonized by approximately 7.5 X 10* bacteria, as demonstrated by Hoppe (1981). Both very large numbers of attached bacteria and countless flagellates, clliates and rotatorians occur in these cyanobacterial agglomerates and contribute to the 02-consumption (Bursa 1968, Gast 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Even if small ciliates can be effective grazers of bacterioplankton, especially the larger size-classes (Gast 1985, Rivier et al 1985, Albright et al 1987, Sherr & Sherr 1987, Sherr et al 1989, Epstein & Shiaris 1992, Simek & Straskrabova 1992, ciliate bacterivory never exceeded 40 % of the total bacterial loss. During Period IV ciliate grazing on bacteria approached zero.…”
Section: Bacterial Lossmentioning
confidence: 99%
“…In addition, grazing by mixotrophic algae (Bird & Kalff 1987, Sanders & Porter 1988, S~lndergaard et al 1988, Bennett et al 1990), heterotrophic ciliates (Gast 1985, Rivier et al 1985, Albright et al 1987, Sherr & Sherr 1987, Sherr et al 1989, and larger zooplankton -in fresh waters especially cladocerans (Geertz-Hansen et al 1987, Christoffersen et al 1990, Wylie & Currie 1991, Jeppesen et al 1992, Vague & Pace 1992) -has also been regarded as potential loss process for picoplankton.…”
Section: Introductionmentioning
confidence: 99%